Epirubicin Enhances the Anti-Cancer Effects of Radioactive 125I Seeds in Hepatocellular Carcinoma via Downregulation of the JAK/STAT1 Pathway - Guo, Lei; Sun, Jiali; Wang, Changjun; Wang, Yang; Wang, Ya; Li, Dong; Li, Yuliang (Frontiers in Oncology, 2022)
The application and promotion of 125I seed implantation technology have increased the safety and effectiveness of the clinical treatment of advanced hepatocellular carcinoma (HCC). Epirubicin (EPI) is a traditional anthracycline chemotherapy agent that has minimal side effects and has been widely used in the clinical treatment of HCC. We hypothesized that EPI would enhance the anti-cancer effects of 125I seeds via the JAK/STAT1 signaling pathway. Thus, we aimed to investigate whether EPI could enhance the radiosensitivity of HCC cells to 125I and determine the underlying molecular mechanism. This basic study was conducted in an animal laboratory at Shandong University. BALB/C male nude mice were used, and all animals were fed and treated according to the standards of the Institutional Animal Care and Use Committee of Shandong University. Both in vitro and in vivo models of 125I irradiation of HCC cells were created. The anti-cancer effects of 125I and the role of EPI in promoting these effects were evaluated using flow cytometry for apoptosis and cell cycle, CCK-8 assay for EPI drug cytotoxicity, and transwell assays for migration and invasion. The potential mediating effect of the JAK/STAT1 pathway was assessed using an isobaric tag for relative and absolute quantitation analysis to identify differentially expressed proteins after 125I treatment. Transfection of HCC cells with STAT1-RNAi were performed to determine the effect of STAT1 downregulation on 125I and EPI treatment effects. The radiosensitivity concentration of EPI promoted 125I-induced anti-cancer effects, including apoptosis, anti-proliferation, and inhibition of migration and invasion. These effects were mediated via the JAK/STAT1 pathway. Downregulation of STAT1 compromised measured anti-cancer effects, which were both confirmed in the in vivo and in vitro models. EPI can promote 125I-induced anti-cancer effects in HCC. The JAK/STAT1 pathway may be a potential target for 125I seed implantation in the treatment of HCC.